Expert System in Determining Disorders of Children with Special Needs at SLBN 1 Bengkulu City Using the Certainty Factor Method - Karno Saputra Hidayat; Maryaningsih Maryaningsih; Rizka Tri Alinse (Jurnal Komputer, Informasi dan Teknologi, 2022)
Bengkulu City 1 Special Special School (SLB) is one of the special schools in Bengkulu City which provides educational facilities ranging from SD, SMP and SMK. Children with special needs at SLB Negeri 1 Bengkulu City are divided into 5 types, namely the Blind, Deaf, Moderately Disabled, Mildly Disabled and Physically Disabled. Students who have just registered at SLB Negeri 1 Bengkulu City are identified with the characteristics of the child to find out the type of disorder in children with special needs. However, in practice this is more difficult than determining the type of normal student disorder in general. This is because each type of child with special needs has some of the same characteristics, so it takes quite a long time. The expert system application at SLB Negeri 1 Bengkulu City was created to assist the school in knowing and determining disorders of children with special needs based on the characteristics experienced by students. The expert system application has been applied to the Certainty Factor Method which is used to obtain the percentage level of certainty for the disorder of the child with special needs. An expert system application for determining disorders of children with special needs at SLB Negeri 1 Bengkulu City is made using the Visual Basic.Net programming language. Based on the results of the tests that have been carried out, the functionality of the expert system application in determining disorders of children with special needs at SLB Negeri 1 Bengkulu City is running well as expected and can provide information on the results of consultations to determine disorders of children with special needs.